PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS SAINS TEKNOLOGI MASYARAKAT (STM) UNTUK MENINGKATKAN KOMPETENSI SISWA DI SDN 1 ALUE DUA - Ida Safitri; Nurul Fadillah (Jurnal Tunas Bangsa, 2021)
This development research aims to produce thematic teaching materials that are feasible and effective to use as additional teaching materials besides textbooks on the theme of living things and the environment. The research was conducted at SDN 1 Alue Dua Langsa. The research sample was students of class V B SDN 1 Alue Dua. The method in this research is the method of research and development (Research and Development) with the Three D (3D) development model. The results of increasing student competence in the form of cognitive abilities using pre-experimental methods with One Group Pretest-Postest Design. The results showed that the additional thematic teaching materials in the form of modules based on Community Science Technology (STM) were declared valid by experts / experts with a validation rate of 84%. Furthermore, there was an increase in students' cognitive abilities which could be seen from the post-test average score increased to 70.5 from the pretest score of 39.27 and the N-Gain score on the high criteria, namely 71.28. So it can be concluded that thematic teaching materials in the form of STM-based modules are feasible to use and have a significant effect on improving the competence of students' cognitive abilities. Abstrak Penelitian pengembangan ini bertujuan untuk menghasilkan bahan ajar tematik yang layak dan efektif digunakan sebagai bahan ajar tambahan selain buku paket pada tema makhluk hidup dan lingkungan. Penelitian dilakukan di SDN 1 Alue Dua Kota langsa dengan sampel penelitian adalah siswa kelas V B SDN 1 Alue Dua. Metode dalam penelitian ini adalah metode penelitian dan pengembangan (Researchand Development) dengan model pengembangan Three D (3D). Hasil peningkatan kompetensi siswa berupa kemampuan kognitif menggunakan metode pre-experimental dengan One Group Pretest-Postest Design. Hasil penelitian menunjukkan bahwa bahan ajar tematik tambahan berupa modul berbasis Sains Teknologi Masyarakat (STM) dinyatakan valid oleh ahli/pakar dengan tingkat validasi sebesar 84%. Selanjutnya terdapat peningkatan kemampuan kognitif siswa yang dapat dilihat dari skor rata rata postes meningkat menjadi 70,5 dari skor pretes 39,27 dan skor N-Gain pada kriteria tinggi yaitu 71,28. Sehingga dapat disimpulkan bahwa bahan ajar tematik berupa modul berbasis STM layak digunakan dan berpengaruh signifikan terhadap peningkatan kompetensi kemampuan kognitif siswa di SDN 1 Alue Dua. Kata Kunci: Bahan ajar, Tematik, Sains Teknologi Masyarakat, Kompetensi